Developing Teacher Training Programs to Meet the Requirements of General Education Innovation in Vietnam - Tu, Hoang Thanh; Hanh, Ninh Thi (VNU Journal of Science: Education Research, 2017)
The implementation of the Communist Party Resolution No.29-NQ/TW on radical and comprehensive innovation in education, serving industrialisation and modernisation has posed two vital tasks to the country’s teacher training institutions: 1) How to train future generations of teachers capable of teaching the new general education curriculum? and 2) How to foster and retrain the current teachers? Based on the survey results and research overview of the two teacher training models (concurrent education model and consecutive education model), this article proposes some measures to develop the training teacher programs meeting the requirements of the general education innovation in Vietnam.